Investigation of the Phenolic Contents and Antioxidant Activities of Some Natural Edible Mushroom Species - KARADENİZ, Mertcan; BAKIR, Temel Kan; ÜNAL, Sabri (Bartin Orman Fakultesi Dergisi, 2024)
In recent years, edible mushroom species have become a part of the daily human diet due to their high protein content. These mushrooms have also gained popularity in alternative medicine practices due to their chemical composition and antioxidant properties. This study aimed to determine the biologically important antioxidant activities and total phenolic content of four different mushroom species, each with its unique appearance and habitat: Amanita caesarea (Aca), Clitocybe geotropa (Cge), Cordyceps militaris (Cmi) and Lentinula edodes (Led). The antioxidant activities of the mushroom species were determined using the DPPH radical scavenging method, and the percentage inhibition and IC50 values were reported. The analysis of inhibition values at various concentrations revealed that both Cmi and Aca mushrooms demonstrated higher antioxidant activity when compared to Led and Cge mushrooms across all tested concentrations. Moreover, the phenolic content of the methanolic extracts, quantified in gallic acid equivalents (GAE), were determined to be 37.04±0.35, 52.04±0.41, 19.33±0.11, and 21.63±0.15 mg GAE/g for Cmi, Aca, Led, and Cge, respectively. In conclusion, a direct correlation was noted between the overall phenolic content and the antioxidant activity of the various mushroom species.
Keywords: Forestry Sciences (Other); DPPH radical scavenging method; Amanita caesarea; Clitocybe geotropa; Cordyceps militaris; Lentinula edodes.; DPPH radikal sönümleme metodu; Amanita caesarea; Clitocybe geotropa; Cordyceps militaris; Lentinula edodes.; Ormancılık (Diğer); 3. Good health